CRIMINAL LIABILITY OF ONLINE GAMBLERS ON THE INVINCIBLE ELEPHANT PLATFORM: Study of Decision No. 1681/Pid.Sus/2024/PN MDN - Simamora, Afric; Manullang, Herlina; Sihotang, Lesson (jfpublisher, 2025)
Gambling, traditionally viewed as a crime, has evolved with the internet, leading to significant social issues, including addiction and financial distress among participants. This research addresses the growing concern of online gambling, particularly on the Invincible Elephant platform, which has become increasingly accessible due to technological advancements. This research focuses on the legal implications and criminal liability of individuals engaging in online gambling activities, as highlighted in Decision No. 1681/Pid.Sus/2024/PN MDN. The rise in online gambling has raised questions on the adequacy of existing laws and the effectiveness of enforcement measures against such activities. This research aims to analyze the criminal liability of online gamblers on the Invincible Elephant platform and to understand the judicial considerations in imposing sanctions on these individuals based on the aforementioned legal decision. This research employs a normative legal methodology, utilizing secondary data that includes primary legal materials, such as the relevant decision and laws, as well as secondary sources like books and journals related to online gambling. The analysis is descriptive, aiming to provide a clear depiction of the issues surrounding online gambling crimes. Findings indicate that online gambling not only poses a risk to individual players, but also contributes to broader societal problems, including increased crime rates and social disruption. It is revealed that the legal framework surrounding online gambling is still evolving, necessitating further regulatory measures to address the challenges posed by this modern form of gambling.